Ameliorating Effect Of Capparis Aphylla Roth In Carrageenan Induced Inflammation In Rats. (International Journal of Environmental Sciences, 2025)
The purpose of this study was to evaluate the capability of Capparis aphylla Roth to lessen inflammation brought by carrageenan in rats. Rats chosen for this experiment were six females of 200–250 g, and each group had six animals, so six groups were formed (n=6). Group 1 did not receive any external treatments, so they drank water and ate a standard diet. The group called Model Control received carrageenan to promote acute inflammation. Group 3 was subjected to carrageenan and also given Indomethacin at a dose of 100 mg/kg. Animals in groups 4, 5, and 6 got carrageenan along with equal amounts of the MECA extract at 190 mg/kg, 240 mg/kg, and 300 mg/kg, respectively. All the required treatments were provided, and staff carefully observed for the whole day. The paws of rats treated with carrageenan became swollen, and this was strongly decreased by the use of Indomethacin as well as MECA. To sustain continuous damage, inflammation goes through processes such as matrix breakdown and formation of new blood vessels. It is one of the most common autoimmune diseases that is known to cause chronic and lasting inflammation, but scientists are unaware of the reason. In RA, the first damage to joints is in the synovial lining, which spreads to the cartilage and bone and causes the formation of a pathological growth called pannus. The process includes evaluating joint scoring, ESR, and CRP, whereas outcome criteria mean paying attention to mortality or x-ray vision of destroyed joints. Reducing the action of COX-II in the body could be the reason for MECA’s anti-inflammatory effects.